Difficulties in Writing Business English Correspondence - Neti Rosiana Fadilah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The title of this research was the difficulties in writing business English correspondence at fourth Secretary Semester students in ASMI Citra Nusantara Banjarmasin Academic Year 2018-2019 which was aimed at knowing the difficulties of Writing Business English Correspondence. The population was 15 students or whole of the fourth Secretary Semester students and the researcher conducted the data using descriptive qualitative research that employs descriptive qualitative method. The data of this study were obtained by using questionnaire was divided into two parts; they are background of the respondent and surveyed the difficulty by using Likert-Scale. The scale ranged from: “Strongly Agree, Agree, Neutral, Disagree and Strongly Disagree”. Writing difficulties at Business English Correspondence at fourth semester students varied in the result which related to the Linguistic difficulty, like wide range of vocabulary usage. They have to enlarge the vocabulary meaning, using appropriate or formal vocabulary or sentences in Business English Correspondence. The respondents also gave their suggestion to change their difficulties like, changed their learning English method especially in writing business English correspondence.